DOES CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE HAVE A ROLE IMPROVE FINANCIAL PERFORMANCE? A PANEL DATA APPROACH (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2022)
This paper explores the effect of Corporate Social Responsibility disclosure on financial performance in Indonesia. Profitability and liquidity used as the primary indicator in measuring financial performance. The sampling technique used in this research was purposive sampling. The research sample was a company listed on the Indonesia Stock Exchange. As a population, there were 721 companies listed on the Indonesia Stock Exchange in 2020. During the 5-year study period, 194 companies met the requirements, for a total of 970 observations. The data were collected by the method of documentation and literature study. The data analysis technique used was panel data regression using Eviews 9. According to the study's findings, CSR disclosure significantly impacted ROA, ROE, and ROI. In addition, CSR disclosure significantly affected QR and Cash R but did not affect CR. Our findings contribute to introducing a primary variable, CSR disclosure, to explain its ability to improve financial performance (profitability and liquidity). We suggest that companies evaluate the effectiveness of CSR activities on the company's financial performance.